2004
DOI: 10.1111/j.1537-2995.2004.03325.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of universal leukoreduction on postoperative infections and length of hospital stay in elective orthopedic and cardiac surgery

Abstract: Implementation of ULR had no major impact on postoperative infection or LOS in patients undergoing elective surgical procedures who received transfusion(s). Smaller effects, either detrimental or beneficial of ULR, cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 35 publications
1
50
1
Order By: Relevance
“…In different studies, LR has been shown to have no effect on infection rates in colorectal surgery [32], elective orthopedic surgery [30], elective cardiac surgery [30,33], or elective major aortic surgery [25]. In-house mortality and LOS have also been shown to be equivalent in a general inpatient population receiving LR versus non-LR blood [34].…”
Section: Discussionmentioning
confidence: 95%
“…In different studies, LR has been shown to have no effect on infection rates in colorectal surgery [32], elective orthopedic surgery [30], elective cardiac surgery [30,33], or elective major aortic surgery [25]. In-house mortality and LOS have also been shown to be equivalent in a general inpatient population receiving LR versus non-LR blood [34].…”
Section: Discussionmentioning
confidence: 95%
“…While five of these studies showed implementation of leukoreduction as associated with decreases in mortality, morbidity and/or costs [80,85,[87][88][89], two studies reported no apparent clinical benefit [88,90]. None of these clinical trials demonstrated any significant increase in morbidity, mortality and/or costs with leukoreduction, thus clearly leukoreduction is cost neutral, at worst [91].…”
Section: Blood Product Manipulationsmentioning
confidence: 94%
“…No clear statement can be made whether universal leukoreduction was indeed associated with any clinical advantage with regard of overall mortality rate, infection rate, or cancer recurrence [74], [75], [76], [77], [78].…”
Section: Clinical Studies On Transfusion-related Immunomodulationmentioning
confidence: 99%